FAMILY - THE BASIS OF A HEALTHY SPIRITUAL ENVIRONMENT AND INFORMATION SECURITY (Universal International Scientific Journal, 2026)
This article examines the family as a foundational social unit for sustaining ahealthy moral environment and strengthening information security. The study employs conceptualanalysis, comparative reasoning, and a qualitative review of secondary sources. Findings indicatethat consistent parenting, trust-based communication, and media literacy act as protective factorsagainst harmful information influences. The paper contributes a family-centered analytical modellinking moral climate to information-risk resilience.
Keywords: family; spiritual environment; information security